2003
DOI: 10.1002/ceat.200301717
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of a Pd‐membrane Reactor for Methanol Synthesis

Abstract: A numerical study is performed in order to evaluate the performance and optimal operating conditions of a palladium membrane reactor for methanol synthesis. A novel reactor configuration with a Pd wall, which is perm-selective to hydrogen, has been proposed. In this configuration the reactants are added to the tube side while pure hydrogen is added to the shell side, as a result, the hydrogen diffuses across the membrane from the shell side to the tube side. In this membrane reactor, hydrogen penetrates to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 10 publications
0
33
0
Order By: Relevance
“…However, there are some attempts of different configuration such as methanol removal [49], and the addition of hydrogen to reaction mixture [46,51]. There are some advantages in using said configurations.…”
Section: Concept Of Membrane Reactor In Co2 Hydrogenation Reactionmentioning
confidence: 99%
“…However, there are some attempts of different configuration such as methanol removal [49], and the addition of hydrogen to reaction mixture [46,51]. There are some advantages in using said configurations.…”
Section: Concept Of Membrane Reactor In Co2 Hydrogenation Reactionmentioning
confidence: 99%
“…Alloying the palladium, especially with silver, reduces the critical temperature for embitterment and leads to an increase in the hydrogen permeability. The highest hydrogen permeability was observed at an alloy composition of 23 wt % silver [27]. The Pd-Ag membrane is single phased after annealing in H 2 at 400 and 500°C and it was reported that the hydrogen permeation rate increases in a single-phase Pd-Ag alloy [28].…”
Section: Introductionmentioning
confidence: 95%
“…There are a few investigations on methanol synthesis in PdAg membrane-type methanol reactors [2,8]. However, there is no information available in the literature regarding the use of a Pd-membrane in an industrial methanol reactor.…”
Section: Introductionmentioning
confidence: 98%
“…Alloying the palladium, especially with silver, reduces the critical temperature for this embitterment and leads to an increase in the hydrogen permeability. The highest hydrogen permeability was observed at an alloy composition of 23 wt % silver [8]. Palladium-based membranes have been used for decades in hydrogen extraction because of their high permeability and good surface properties and because palladium, like all metals, is 100 % selective for hydrogen transport [9].…”
Section: Introductionmentioning
confidence: 99%